DIGITAL MARKETING: a competitive tool in the covid-19 pandemic - Caracini, Luiz Gustavo (Revista Interface Tecnológica, 2023)
This work will illustrate the importance of digital marketing as a competitive tool during the pandemic. The study presents a qualitative analysis of the results obtained through comparative data, taken from research of scientific articles, matter and publications related to the proposed theme. Data obtained from several research centers on the topic discussed. The results indicate that digital marketing became even more relevant during the pandemic, as people began to consume more online content and use social media more. In addition, the article presents some of the main digital marketing strategies used by companies during the pandemic, such as the creation of relevant content, the use of social networks to engage the public, the investment in paid advertisements and the use of marketing automation tools. marketing. Analyzing the data, we identified that companies that were able to adapt to this new reality and invest in digital marketing strategies were able to stand out in the market and win new customers.
Keywords: Digital Marketing; Pandemic; Strategies; Adaptation; Marketing; Social Networking